2014
DOI: 10.1016/j.nuclphysa.2014.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear PDFs in the beginning of the LHC era

Abstract: The status of the global fits of nuclear parton distributions (nPDFs) is reviewed. In addition to comparing the contemporary analyses of nPDFs, difficulties and controversies posed by the neutrino-nucleus deeply inelastic scattering data is overviewed. At the end, the first dijet data from the LHC proton+lead collisions is briefly discussed.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 104 publications
(120 reference statements)
1
24
0
Order By: Relevance
“…While the quark nPDF of lead ions (Pb) is well understood from deep inelastic scattering data [8], the gluon nPDF, which is particularly important for perturbative QCD (pQCD) calculations at the CERN LHC energies, is not well constrained. This is because of the limited amount of experimental data that are sensitive to the nPDFs of gluons at perturbative scales [9,10]. The pion spectra in deuteron-gold collisions at a nucleon-nucleon center-of-mass energy √ s NN = 200 GeV [11,12] are the only relativistic heavy ion collision data from the BNL RHIC used in the global fits of nPDFs.…”
mentioning
confidence: 99%
“…While the quark nPDF of lead ions (Pb) is well understood from deep inelastic scattering data [8], the gluon nPDF, which is particularly important for perturbative QCD (pQCD) calculations at the CERN LHC energies, is not well constrained. This is because of the limited amount of experimental data that are sensitive to the nPDFs of gluons at perturbative scales [9,10]. The pion spectra in deuteron-gold collisions at a nucleon-nucleon center-of-mass energy √ s NN = 200 GeV [11,12] are the only relativistic heavy ion collision data from the BNL RHIC used in the global fits of nPDFs.…”
mentioning
confidence: 99%
“…An outstanding, and still unresolved, issue in nuclear DIS was highlighted in 2011 by the nCTEQ collaboration, who observed that using nPDFs fitted to lepton-nucleus data it is not possible to reproduce the data in neutrino-nucleus scattering [52], see FIure 7. The EPS group do not observe the same tension between neutral and charged current scattering [53,54], although they do not take into account correlated errors in the NuTeV data. The ensuing debate has not yet been settled.…”
Section: Pos(dis2015)001mentioning
confidence: 97%
“…Current nPDF fits typically have high energy applications in mind [54], and naively treat nuclei as a collection of Z unbound proton and A − Z neutron targets in regard to the treatment of the kinematics, and assume universality of the nuclear parton distributions. However, as the observed "non-scaling" behavior of light nuclei at JLab and the discussion on neutral vs. charged current data highlight, this may not be the case.…”
Section: Pos(dis2015)001mentioning
confidence: 99%
“…Similarly, e ± +A DIS scattering experiments at an EIC [54] will extract the nuclear PDFs (nPDFs) [55,56], that are important for a deeper understanding of heavy-ion collisions. So far, the kinematic reach of the available fixed target e ± +A cross-section measurements is much more restricted than for protons, with very little data available for low x ≤ 10 −2 at Q 2 ∼ 10 GeV 2 .…”
Section: Structure Functions In Nucleimentioning
confidence: 99%